PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 184 PEKANBARU - Rahmawati, Fahruniza; Witri, Gustimal; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of the problem in this research was the poor studentsâ achievements in mathematics, it can be seen on studentsâ mathematics scores. There were 21 of 36 students who had not achieved the Achievement Standard (58,33%), while the ones who achieved were only 15 students (41,67%), and the average scores of the class was 62.22. The Achievement Standard that school determines is 70. Based on the problem, the researcher had conducted class action research by implementing cooperative learning which is pairs checks. At the first meeting in cycle I, the percentage of teachersâ activity was 66.66% which is categorized as enough. At the second meeting, the percentage increased to 69.44% which is categorized as enough. At the first meeting in cycle I, the percentage increased to 88.89% that is categorized as good. At the second meeting the percentage increased to 97,22% which is categorized as very good. The studentsâ activities had increased. At the first meeting in cycle I, the studentsâ activities gained 63,39% which is categorized as enough, while at the second meeting in cycle I the studentsâ activities gained 66,67% which is categorized as enough. At the first meeting of cycle II, the percentage increased to 88.89% that is categorized as good, while at the second meeting the percentage increased to 94.44% which is categorized as very good. The average of studentsâ achievements before the implementation was 62.22 which increased to 73.61 in cycle I, and increased again to 87.22 in cycle II. The completeness in cycle I and cycle II was achieved. It is concluded that the implementation of cooperative learning pairs checks type can improve students achievements in mathematics of grade four at SDN 184 Pekanbaru.Key Words: Cooperative Learning Pairs Checks Type, Achievements In Mathematics